Penerapan Analisis SWOT Dalam Meningkatkan Penjualan Produk Baslok Echo Bekasi Pada Era Persaingan - Nurazizah, Rizty Dwi; Yunita, Tyna (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
To increase sales, companies must understand customer demands and preferences. Consumers are now more selective, so better products and affordable prices influence their choices. SWOT analysis is a basic tool that can help businesses achieve these goals. This analysis is based on reasoning that can minimize dangers and weaknesses while optimizing opportunities and strengths. This research aims to ensure that Baslok Echo Bekasi can survive and compete with the strategies used, including maintaining original taste quality, providing maximum service, and following trends. So you can find out what products and strategies are implemented by Baslok Echo to increase its sales using SWOT analysis. Two methods of data collection were used in this research: study observation and literature review. Based on the SWOT matrix analysis table, Baslok Echo MSMEs have strong competitiveness because of the advantages and possibilities they have.